2001
DOI: 10.1016/s0896-6273(01)00461-5
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Site of Acetylcholine Receptor as Visualized in the X-Ray Structure of a Complex between α-Bungarotoxin and a Mimotope Peptide

Abstract: We have determined the crystal structure at 1.8 A resolution of a complex of alpha-bungarotoxin with a high affinity 13-residue peptide that is homologous to the binding region of the alpha subunit of acetylcholine receptor. The peptide fits snugly to the toxin and adopts a beta hairpin conformation. The structures of the bound peptide and the homologous loop of acetylcholine binding protein, a soluble analog of the extracellular domain of acetylcholine receptor, are remarkably similar. Their superposition ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
140
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(147 citation statements)
references
References 46 publications
6
140
1
Order By: Relevance
“…Clearly the loop C that contains highly functional residues conserved in both receptors plays a predominant binding role. The evidence that supports that conclusion includes (i) mutational analyses with short chain (33,34) and long chain (35)(36)(37) toxins, (ii) the use of synthetic receptor peptides of the region 180-200 (38,39), (iii) studies on the resistance of various species to toxins (40,41), (iv) direct affinity labeling experiments (42), and (v) resolution of solution structures of the complexes formed between ␣-Bgtx and peptides (32,(43)(44)(45). Also, the additional binding function observed here for other ␣ and non-␣ loops was postulated for muscular receptors (46)(47)(48).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Clearly the loop C that contains highly functional residues conserved in both receptors plays a predominant binding role. The evidence that supports that conclusion includes (i) mutational analyses with short chain (33,34) and long chain (35)(36)(37) toxins, (ii) the use of synthetic receptor peptides of the region 180-200 (38,39), (iii) studies on the resistance of various species to toxins (40,41), (iv) direct affinity labeling experiments (42), and (v) resolution of solution structures of the complexes formed between ␣-Bgtx and peptides (32,(43)(44)(45). Also, the additional binding function observed here for other ␣ and non-␣ loops was postulated for muscular receptors (46)(47)(48).…”
Section: Discussionmentioning
confidence: 98%
“…However, the manner by which the toxin interacted with the receptor complementary face differed substantially in both studies. In particular, structural clashes appeared in the AChBP-␣-Bgtx complex model (32) between the toxin and the receptor loops D, F, and 1, excluding the possibility that the toxin recognizes the receptor (AChBP) in this conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies to the MIR efficiently crosslink adjacent AChRs, not the two ␣1 subunits within an AChR, because the MIR is oriented in a way that only permits crosslinking of adjacent AChRs. Antibodies bound to the MIR do not compete with ligands of the ACh binding site because the binding sites are half way up the side of the AChR at the interface of the plus side of ␣1 subunits and the minus side of ␦ and ⑀ subunits ) and because bound ␣-bungarotoxin occludes only a small area near the ACh binding site (Harel et al, 2001). Thus, the MIR antibodies are not competitive antagonists, and they do not interfere with the binding of 125 I␣-bungarotoxin used to label AChR for immunodiagnostic assays for MG. Antibodies to the MIR are not allosteric antagonists because they bind within one subunit, well away from the channel, and away from subunit interfaces where conformation changes may take place between resting, activated, and desensitized forms of the AChR.…”
Section: Pathological Significance Of the Mirmentioning
confidence: 99%
“…Electrophysiology experiments on the nAChRs expressed in Xenopus oocytes revealed that the first chimera and neurotoxin I block ␣7 nAChRs with similar potency (IC 50 6.1 and 34 nM, respectively). Therefore, the disulfide-confined loop endows neurotoxin II with full activity of long-chain ␣-neurotoxin and the C-terminal tail in neurotoxin I is not essential for binding.…”
mentioning
confidence: 99%